Penerapan New Public Management di Pendidikan Tinggi Studi Kasus di STIA & P Annisa Dwi Salfaritzi Palembang - Fahlevi, Rizal; Satispi, Evi (Jurnal Pemerintahan dan Politik, 2024)
New Public Management offers a different perspective to improve public sector performance by adopting the work spirit of the private sector which prioritizes the values of efficiency and effectiveness. This problem gave rise to the idea of how to implement new public management in higher education by taking a case study at the Annisa Dwi Salfarizi College of Administration and Government in Palembang. This research aims to determine the application of new public management in higher education, especially at the Annisa Dwi Salfarizi College of Administration and Government, Palembang. The method used in this research is research with a qualitative approach, namely building arguments to obtain and sort data as well as interpret and conclude data findings. The data in this research was collected through observation and interviews. The results of the research were that the Annisa Dwi Salfarizi Palembang College of Administration and Government carried out face-to-face lectures using power points, tuition payments were still made manually, and KRS was filled out in writing rather than using an integrated system. system. Academic activity information services are announced through information posted on the notice board, so students must always check the notice board regularly and must come to campus if they want to find out information about lectures. Conclusion: The implementation of New Public Management in Higher Education using case studies at the Annisa Dwi Salfarizi College of Administration and Government in Palembang does not appear to have been implemented optimally.